2012
DOI: 10.1590/s0100-879x2012007500091
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral meaningful opioidergic stimulation activates kappa receptor gene expression

Abstract: The periaqueductal gray (PAG) has been reported to be a location for opioid regulation of pain and a potential site for behavioral selection in females. Opioid-mediated behavioral and physiological responses differ according to the activity of opioid receptor subtypes. The present study investigated the effects of the peripheral injection of the kappa-opioid receptor agonist U69593 into the dorsal subcutaneous region of animals on maternal behavior and on Oprk1 gene activity in the PAG of female rats. Female W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
(32 reference statements)
0
6
0
1
Order By: Relevance
“…As a receptor for oxytocin, AVPR1A was shown to mediate the secretion of ACTH and PRL by binding AVT to finely regulate ovulation in chickens [31]. Expression levels of OPRK1 were closely related to oocyte maturation [32] and maternal behavior [33]. LPAR3 could interact with multiple reproductive hormones, including progesterone [34], estrogen [35], and prostaglandin [36,37], to affect reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…As a receptor for oxytocin, AVPR1A was shown to mediate the secretion of ACTH and PRL by binding AVT to finely regulate ovulation in chickens [31]. Expression levels of OPRK1 were closely related to oocyte maturation [32] and maternal behavior [33]. LPAR3 could interact with multiple reproductive hormones, including progesterone [34], estrogen [35], and prostaglandin [36,37], to affect reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Direct injection of the κ agonist U69593 into the dorsal periaqueductal gray (PAG) stimulated maternal behavior and KOR gene expression. No changes were observed in the δ or μ receptors [43] .…”
Section: Kop In Depression and Anxietymentioning
confidence: 77%
“…The present study evaluated the basal pattern of Oprm1 , Oprk1 , and Oprd1 gene expression in female rat brain sites that are known to be involved in reproductive behavior, including the striatum (i.e., important role in motor patterns during mating and lactation), PAG (i.e., role in nociception, behavioral selection for motivated behaviors, and sexual and maternal behavior), and hypothalamus (i.e., role in the modulation of hormonal aspects) (Sewards and Sewards 2003 ; Moura et al 2010 ; Mota-Ortiz et al 2012 ; Teodorov 2012 ). Studies have shown that estrogen is able to change the action of the opioidergic system in rodents by modulating nociceptive responses to treatment with naloxone, altering the binding of opioid receptors in specific brain regions, and increasing the rate of internalization of these receptors, particularly in morphine studies (Hammer 1990 ; Gordon and Soliman 1996 ; Aloisi and Ceccarelli 1999 ; Micevych et al 2003 ).…”
Section: Discussionmentioning
confidence: 99%